Development of a large-scale torsional split Hopkinson tube for dynamic shear test of mortar material. Issue 3 (4th March 2023) - He, Jing; Hong, Jian; Chen, Li; Yu, Xiao; Jiang, Xiquan; Fang, Qin; Xiang, Hengbo
Abstract : Due to the lack of reliable dynamic shear test technology, there are few studies on dynamic pure shear performance of concrete materials. Based on the one-dimensional stress wave propagation theory, a large-scale torsional split Hopkinson Tube (LTSHT) with an outer diameter of 110 mm was developed. The LTSHT comprises a bearing system, an axial driving system, a four-lug symmetrical impact loading system, an incident tube, and a transmission tube. Numerical simulations showed that the LTSHT produced a well-defined torsional wave, and the bending wave was very small when the lug-error was not more than 0.05 mm. Furthermore, a data measurement and processing of the LTSHT were proposed. Dynamic pure shear tests with shear strain rate ∼14 s −1 on three thin-walled mortar specimens were conducted. The failure process was recorded. The dynamic shear strength was ∼8 MPa and shear stress–strain curves of the three thin-walled mortar specimens showed great repeatability.